Molecular dynamics simulation of strengthening of nanocrystalline Cu alloyed with Zr. (March 2021) - Wu, Cheng-Da; Li, He-Xing
Abstract: Nanocrystalline Cu-Zr alloys are an emerging class of immiscible high-strength materials with significant potential for structural and high-temperature applications. The effects of Zr concentration and tensile velocity on the strengthening and mechanics of Cu alloyed with Zr is studied using molecular dynamics simulations based on the many-body embedded-atom potential. The simulation results show that the potential energy of Cu-Zr systems significantly decreases with increasing Zr concentration, resulting in an increase in structural stabilization. Doping Zr atoms at the grain boundaries can strengthen the boundaries and reduce their mobility during the tensile test. The Young's modulus of Cu-Zr systems decreases with increasing Zr concentration. The plasticity of Cu-Zr systems increases with increasing Zr concentration. The mechanical strength of Cu-Zr systems reaches its maximum value, which is 1.13 times that of the pure Cu counterpart, when the Zr concentration is 5%.